2019
DOI: 10.3389/fphar.2019.01223
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Review on Phytochemicals, Pharmacological and Clinical Potentials of Gymnema sylvestre

Abstract: Gymnema sylvestre is a plant included in Apocynaceae family and is located in many regions of Asia, Africa and Australia. This plant is widely used as a traditional therapy for different purposes. Even now it is being used as a dietary supplement due to its numerous therapeutic uses. It is known to have blood glucose lowering potential and, thus, is widely used in traditional and Ayurvedic systems of medicine. It renders glucose lowering activity due to the presence of phytochemicals, such as gurmarin, gymnemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 106 publications
0
68
0
Order By: Relevance
“…The phytoconstituents of G. sylvestre consist of many groups containing bioactive compounds that are listed in the below table ( Table 3 ) [ 112 , 113 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
See 2 more Smart Citations
“…The phytoconstituents of G. sylvestre consist of many groups containing bioactive compounds that are listed in the below table ( Table 3 ) [ 112 , 113 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
“…The major biological active ingredient of G. sylvestre is Gymnemic acids—a group of triterpenoid saponins isolated and identified successfully ( Figure 11 ). Several studies have reported that the main biological activity of this plant is antidiabetic activity [ 113 ].…”
Section: Bioactive Compounds From Plants Having Type 2 Antidiabetimentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo investigation G. sylvestre revealed the pharmacological potentials including antidiabetic and hypoglycemic, antihyperlipidemic, antioxidant, anti-inflammatory, antiarthritic, anticancer, antimicrobial, hepatoprotective, cardioprotective, and immunosuppressive activities [ 8 ]. These actions are attributed to the therapeutically essential families of compounds, including polyphenols, flavonoids, kaempferol, quinones, anthraquinones, tannins, triterpenoid saponins, and gymnemic acids [ 9 ]. Gymnema inodorum (Lour.)…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is linked with hepatic complications such as acute liver disease, raised liver enzyme levels and nonalcoholic fatty liver (Khan et al, 2019). The current study has explored the effect of CBSKE and GSLE separately and in combination on hepatic and lipid profiles in alloxanized diabetic rats.…”
Section: Discussionmentioning
confidence: 99%